Transesterification of used cooking oil by palm lignocellulosic biomass magnetic biochar catalyst : Optimization and kinetic analysis - Mohd Nurfirdaus, Mohiddin; Tan, Yie Hua; Jibrail, Kansedo; Nabisab Mujawar, Mubarak; Chan, Yen San; Mohammad, Khalid; Lee, Keat Teong (Elsevier Ltd., 2024)
Biodiesel has recently gained popularity as an alternative biofuel to substitute fossil fuel. Utilization of magnetic biochar catalyst (MBC) in biodiesel production can enhance the catalyst separation process. In this research, MBC was synthesized from oil palm waste such as palm kernel shell (PKS), oil palm frond (OFP), and empty fruit bunch (EFB). Biodiesel production parameters were studied using the Central Composite Design-based Response Surface Method. Based on the characterization results, EFB is the most suitable palm lignocellulosic biomass for MBC synthesis. The MBC has a BET surface area of 44.42 m2 g−1, an average acid density value of 3.85 mmol g−1, and a σs value of 3.19 Am2 kg−1. MBC synthesis is at its optimal by using 1.5 M FeCl3·6H2O solution, 800 °C carbonization temperature, and 2.5 M H2SO4. The optimized transesterification parameters are: catalyst loading of 10.25 wt%, methanol to oil molar ratio of 28, 70 °C, and 8 h gave a maximum fatty acid methyl ester yield of 91.50 %. After five cycles, the yield dropped to 67.37 %. Biodiesel production is reported to be the pseudo-irreversible first-order kinetic with an activation energy of 29.20 kJ mol−1. The physicochemical characterization showed the biodiesel has met the ASTM D6751 standard.